Cho các đa thức f(x)=2x^2+3x-5 và g(x)=3x^2+2x-7
a)Tính f(-2)
b)Tính f(x)+g(x)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
bài 1:
a) ta có: 3x + 5 = (3(x+1)+2)\(⋮\)(x+1)
vì (3(x+1)\(⋮\)(x+1) nên 2 \(⋮\)(x+1) => (x+1) \(\in\)Ư(2) => (x+1) \(\in\)\(\xi\)-2;-1;1;2 \(\xi\)=> x \(\in\)\(\xi\)-3; -2; 0; 1 \(\xi\)
vậy, x= -3; -2; 0; 1
x3 + 3x - 4 = 0
=> x3 - x2 + x2 - x + 4x - 4 = 0
=> x2 ( x - 1 ) + x ( x - 1 ) + 4 ( x - 1 ) = 0
=> ( x2 + x + 4 ) ( x - 1 ) = 0
\(\Leftrightarrow\orbr{\begin{cases}x^2+x+4=0\\x-1=0\end{cases}\Leftrightarrow}\orbr{\begin{cases}x^2+x=-4\left(loai\right)\\x=1\end{cases}}\)
c. - x ( x + 3 ) + 2 = ( 4x + 1 ) ( x - 1 ) + 2x
<=> - x2 - 3x + 2 = 4x2 - x - 1
<=> 4x2 - x - 1 + x2 + 3x - 2 = 0
<=> 5x2 + 2x - 3 = 0
<=> ( 5x2 + 5x ) - ( 3x + 3 ) = 0
<=> 5x ( x + 1 ) - 3 ( x + 1 ) = 0
<=> ( 5x - 3 ) ( x + 1 ) = 0
\(\Leftrightarrow\orbr{\begin{cases}5x-3=0\\x+1=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{3}{5}\\x=-1\end{cases}}\)
d. ( 2x + 3 ) ( x - 3 ) - ( x - 3 ) ( x + 1 ) = ( 2 - x ) ( 3x + 1 ) + 3
<=> ( x - 3 ) ( 2x + 3 - x - 1 ) = - 3x2 + 5x + 5
<=> x2 - x - 6 = - 3x2 + 5x + 5
<=> - 3x2 + 5x + 5 - x2 + x + 6 = 0
<=> - 4x2 + 6x + 11 = 0
\(\Leftrightarrow x=\frac{6\pm\sqrt{\left(-6\right)^2-4\left(4.\left(-11\right)\right)}}{2.4}\)( xài công thức bậc 2 )
\(\Leftrightarrow x=\frac{6\pm2\sqrt{53}}{8}\Leftrightarrow x=\frac{3\pm\sqrt{53}}{4}\)
Vậy \(x=\frac{3+\sqrt{53}}{4};x=\frac{3-\sqrt{53}}{4}\)
a) \(f\left(-2\right)=2.\left(-2\right)^2+3.\left(-2\right)-5\)
\(f\left(-2\right)=8-6-5=-3\)
b) \(f\left(x\right)+g\left(x\right)\)
\(=2x^2+3x-5+3x^2+2x-7\)
\(=5x^2+5x-12\)